2011
DOI: 10.1021/ml100302t
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Donor Doxorubicins Accumulate into Doxorubicin-Resistant Human Colon Cancer Cells Inducing Cytotoxicity

Abstract: Products 4 and 5, obtained by conjugation of doxorubicin with nitric oxide (NO) donor nitrooxy and phenylsulfonyl furoxan moieties, respectively, accumulate in doxorubicin-resistant human colon cancer cells (HT29-dx), inducing high cytotoxicity. This behavior parallels the ability of the compounds to generate NO, detected as nitrite, in these cells. Preliminary immunoblotting studies suggest that the mechanism that underlies the cytotoxic effect could involve inhibition of cellular drug efflux due to nitration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 16 publications
(37 reference statements)
4
73
0
2
Order By: Relevance
“…25,26 Since multidrug resistance transporters (MDR) are considered potentially attractive targets for the development of new antischistosomal drugs, 13 selected members of this new class of PZQ/furoxan hybrid products are worthy of additional investigation, in view of their potential activity against PZQ-resistant schistosomes.…”
Section: Resultsmentioning
confidence: 99%
“…25,26 Since multidrug resistance transporters (MDR) are considered potentially attractive targets for the development of new antischistosomal drugs, 13 selected members of this new class of PZQ/furoxan hybrid products are worthy of additional investigation, in view of their potential activity against PZQ-resistant schistosomes.…”
Section: Resultsmentioning
confidence: 99%
“…Other in vitro studies on prostate cancer cell lines and a three-dimensional model of breast cancer relate the effect of NO donors on the level of hypoxia and chemosensitivity (11)(12)(13). An alternative mechanism of NO donors in combination with antitumor agents was reported by Chegaev et al (14), where it was observed that NO donors prevented the activation of proteins associated with drug resistance, such as the P-glycoprotein, in the HT29 colorectal cancer cell line resistant to doxorubicin (14). Considering the possible effect of NO-donors as therapy sensitizers, the combination of Discussão O potencial efeito antitumoral dos compostos L1 e L2 foi avaliado em células MDA-MB-231, uma linha celular humana representativa de cancro de mama agressivo.…”
Section: Discussionmentioning
confidence: 93%
“…Outros estudos in vitro em linhas celulares de cancro da próstata e num modelo tridimensional de cancro de mama descrevem o efeito dos dadores de NO ao nível da hipoxia e quimiossensibilidade (11)(12)(13). Um mecanismo alternativo de dadores de NO em combinação com agentes antitumorais foi relatado por Chegaev et al (14), onde se observou que os dadores de NO impediram a ativação de proteínas associadas à resistência a fármacos, como a glicoproteína-P, na linha celular L1 and L2 with chemotherapy or radiotherapy should be also considered in future studies. NO donors may also influence cell invasiveness, as can be seen in a study by Postovit et al (15).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…It is well-known that high levels of NO can act as a potent anti-cancer agent by promoting apoptosis, inhibiting angiogenesis, and sensitizing tumor cells to chemotherapy, radiation, and immunotherapy [3][4][5][6]. High concentration of NO was also reported to reverse the resistance to doxorubicin in human colon cancer cells [7,8]. Furoxan is an important class of NO donors, which can release high levels of NO in vitro [9].…”
Section: Introductionmentioning
confidence: 99%